Computed Tomography Perfusion Identifies Patients With Stroke With Impaired Cardiac Function. Issue 2 (February 2020) - Garcia-Esperon, Carlos; Spratt, Neil J.; Gangadharan, Shyam; Miteff, Ferdinand; Bivard, Andrew; Lillicrap, Thomas; Tomari, Shinya; Levi, Christopher R.; Parsons, Mark W.
Abstract : Background and Purpose—: Low left ventricular ejection fraction (LVEF) leads to worse outcomes after stroke. We hypothesized that the arterial input function (AIF) variability on perfusion computed tomography, especially the time between scan onset and end of AIF (SO-EndAIF), would reflect reduction of cardiac output. Methods—: Retrospective analysis of consecutive stroke patients, who underwent computed tomography between January 2013 and September 2018, was performed in 2 parts. (1) To determine the correlation between SO-EndAIF and LVEF, all patients with a transthoracic echocardiogram performed ±6 months from the time of stroke were included. LVEF was dichotomized as either normal (≥50%) or decreased (<50%). (2) AIF was compared with hypoperfusion volume, defined as delay time >3 seconds and with clinical outcome measured using 3-month modified Rankin Scale. Results—: A total of 732 ischemic stroke patients underwent computed tomography, 231 with transthoracic echocardiogram were included in part (1), 393 with outcome data were included in part (2). In part (1), 193/231 (83.5%) had normal LVEF (median 61%) and 38/231 (16.5%) decreased LVEF (median 39%). The low-LVEF group had significantly prolonged SO-EndAIF compared with normal-LVEF group (mean of 39.7 versus 26 second; P <0.001), and larger hypoperfusion lesions (94.9 versus 37.6 mL; P <0.001). SO-EndAIF time was strongly associated with EF, with an area under the curve of 0.86. Twenty nine seconds was the best threshold to distinguish between normal and impaired EF (area under the curve, 0.77). In part (2), the SO-EndAIF ≥29 second group had larger hypoperfusion volumes (21.8 versus 89.7 mL; P <0.001) and infarct core (12.2 versus 2.3 mL; P <0.0001) and patients with SO-EndAIF ≥29 seconds had fewer excellent or good clinical outcomes (modified Rankin Scale score 0–1; 40% versus 22%; OR, 2.79; P <0.001, modified Rankin Scale score 0–2; 65% versus 35%; OR, 1.41; P =0.033). Conclusions—: AIF width correlates with ejection fraction in acute ischemic stroke. A 29-second threshold from scan onset to end of AIF accurately predicts reduced LVEF and identifies patients more likely to have worse outcomes after stroke. Abstract : Supplemental Digital Content is available in the text.